Comparison of the Effect of Probiotic Powder, Probiotic Liquid, and Probiotic Combination on Broiler Carcass Quality and Carcass Percentage - Susanti (Bantara Journal of Animal Science, 2024)
A key factor in accomplishing the SDGs is the livestock industry and broiler chicken farming. Zero hunger is one of the SDGs' goals, and it enhances nutrition to support food security in the livestock and agricultural sectors. It's intriguing to research the usage of probiotics as a booster in chicken feed addition. The purpose of this study was to determine how adding probiotic-based liquid, powder, and combination affected the quality and percentage of the carcass weight. Under a fully Randomized Design in a 4 x 4 factorial layout, one hundred Ross broilers were randomly split into four groups (five replicates per treatment and five birds per replicate). T0 is the control group (no probiotics), T1 is the baseline diet plus probiotic powder (50 mg/kg), and T2 is the drinking water plus probiotic liquid (1 mL/L). and T3= Combination (Liquid probiotic + drinking water 1 mL/L) and Powder-based utilized Basal diet + probiotic powder 50 mg/Kg. Duncan was employed in additional tests. Probiotics can increase the percentage of carcass and the quality of the carcass weight. T3 is the most effective treatment in terms of carcass weight and percentage of the carcass.